An investigation on powder stream in Cold Gas Spray (CGS) nozzles - LUPOI, ROCCO (My University, 2011)
The exponential increase of industrial demand in the past two decades has led scientists to th e development of alter native technologies for th e fast manufacturing of engineering components, aside from standar d and time consuming techniques such as casting or forging. Cold Gas Spray (CGS) is a newly d eveloped manufacturing technique, based upon the deposition of metal powder on a substrate due to high energy impacts. In this process, the powder is accelerated up to supersoni c speeds in a converging-diverging nozzle, typically employing air, nitrogen or helium as carrier gas. Recent developments have demonstrated significant process capabilitie s, from the building of mould-free 3D shapes made of various metals, to low porosity and corrosion resistant coatings of titanium. In the CGS process, the particle stre am characteristics during the acceleration process become important in relation w ith the final geometry of the coating. Experimental studies have show n the tendency of particles to spread over the nozzle acceleration channel, resulting in a highly dispersed stream. This paper presents an investigation on the powder stream characteristics in CGS supersonic nozzles. The powder injection loca tion was varied within the carrier gas flow, along with the geometry of the powder in jector, in order to id entify their relation with particles trajectories. Computational Fluid Dynamic (CFD) results are presented, along with experimental observations
CFD-ECCOMAS
Keywords: Fluid Dynamics; CGS; Powder stream; Coatings